Quality research papers: for students of religion and theology - Vyhmeister, Nancy J. (Zondervan, 2007)
Nancy Vyhmeister's Quality Research Papers is fast becoming a standard reference textbook for writing research papers in the field of religion and theology. It takes the student from the beginning assignment of a paper through the research phase to the finished paper. This second edition gives improvements and added material for such things as the expanding field of online research and doing church-related research in a professional manner. Resources for doing research are updated throughout the book.